The capoeira social memory: History and narratives - Costa, Marcelo; Silva, Sergio Luiz (FCL-UNESP Laboratório Editorial, 2021)
The theme proposed by this article is the social memory of capoeira andits presence in the Baixada Fluminense region -RJ, Brazil. Its objective is to understandthe following issues: (i) the context of migration of capoeira to this region; (ii) theemergence of capoeira in Baixada Fluminense and; (iii) the places capoeira hasoccupied and has been occupying. The capoeira was present in important historicalmoments of the country. However, in the relationship of power between the dominantand the dominated, it was persecuted and prohibited. This attempt to social exclusionleft traces and vestiges which, through academic, archivist and ethnographic research,have been building the memory of capoeira in different locations. This is the case of thepresence of capoeira in Baixada Fluminense region, which, through the memory of itsmasters, has been gaining visibility.